Pengaruh Customer Experience dan Customer Value terhadap Repurchase Intention di The Balcone Suites & Resort - Liza Nuryanti; Waryono Waryono (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This research is motivated by the phenomenon of repurchase intention caused by customer experience and customer value. The purpose of this study is to analyze the influence of customer experience and customer value on repurchase intention at The Balcone Suites & Resort. The research method used in this study is quantitative descriptive research with a causal-associative approach. The population of this study consisted of guests staying at The Balcone Suites & Resort, with a sample size of 120 respondents selected using Purposive sampling techniques. The study instrument used in this study was a questionnaire with a Likert scale. The data obtained were analyzed using SPSS version 26.00 and the results of the analysis are presented in tabular form. The results of this study are: Customer experience is rated 86.5% in the "very good" category, customer Value are rated 85.5% in the "very good" category and repurchase intention is rated 86.3% in the "very good" category. Multiple linear regression tests with T-tests for customer experience and customer value variables have an effect on the repurchase intention variable at The Balcone Suites & Resort. The F-test value of customer experience and customer value variables simultaneously has an effect on the repurchase intention variable at The Balcone Suites & Resort. The adjust R square value of 0,621 means that 62% of the customer experience (X1) and customer value (X2) variables influence repurchase intention variable (Y), while the remaining 38% is influenced by other factors outside this research model. The implementation of the results of this study is that the management of The Balcone Suites & Resort can improve the quality of services and facilities to ensure a positive guest experience, as well as evaluate pricing strategies to increase guest perceived value, thereby encouraging repeat purchase intentions.